Writing development in K-Pop stan Twitter communities - Dinda Alifia Darmawan; Lidiyatul Izzah (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2022)
This research focuses on the use of language in social interactions, specifically within the context of K-Pop fans using social media platform Twitter to communicate with other fanbases. The study aims to determine the impact of the K-Pop community on Twitter on the writing skills of high school students in English. The research method employed is quantitative, using a sample of 100 high school students who are members of the K-Pop community on Twitter for at least a year and have studied English. Data was collected using a Likert scale. Results of the analysis indicate a significant effect of the Twitter community on the development of student's writing skills in English Keywords: Twitter; K-Pop; Writing